Bacteria as an alternate biofactory for carotenoid production: A review of its applications, opportunities and challenges. (April 2020) - Ram, Shristi; Mitra, Madhusree; Shah, Freny; Tirkey, Sushma Rani; Mishra, Sandhya
Graphical abstract: Highlights: Bacteria are an irrefutable competitor for existing carotenoid source. Carotenoid are associated with diverse health benefits. Stress triggers selective carotenoid accumulation as defence response. SWOT analysis targeting perils and promises of bacterial carotenoid. Abstract: Carotenoid has gained a reputation amongst researchers for its robust antioxidant capabilities. This review reasons the inevitability of carotenoid for a larger role than just dietary supplements. In an era dominated by chemical or plant-derived carotenoid, bacterial carotenoid provides a compelling forte to be exploited as a promising alternative. Bacteria are amazingly resourceful beings; however, their low carotenoid content makes them undesirable for commercial applications. Here, we have reviewed their applications as a strong prophylactic agent in the health sector with a myriad of applications. Additionally, various measures for augmenting carotenoid yield through new-age technologies, like sequential nutrition starvation, the induction of carotenoid accumulation in microbial cells by employing several stress factors, and the construction of hyper-carotenoid producing strains through genetic engineering for creating proficient producers have been offered. Finally, SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis has been presented to perceive the significance of four major components involved in its commercialisation.